The Halophyte Halostachys caspica AP2/ERF Transcription Factor HcTOE3 Positively Regulates Freezing Tolerance in Arabidopsis - Yin, Fangliu; Zeng, Youling; Ji, Jieyun; Wang, Pengju; Zhang, Yufang; Li, Wenhui (Frontiers in Plant Science, 2021)
The APETALA 2 (AP2) and ethylene-responsive element binding factor (ERF) gene family is one of the largest plant-specific transcription factor gene families, which plays a critical role in plant development and evolution as well as response to various stresses. The Target of eat 3 (TOE3) gene is derived from Halostachys caspica and belongs to the AP2 subfamily with two DNA binding domains. Currently, AP2 family mainly plays crucial roles in plant growth and evolution, yet there are few reports about the role of AP2 in abiotic stress tolerance. Here, we report HcTOE3, a new cold-regulated transcription factor gene, which has an important contribution to freezing tolerance. The main results showed that the expression of HcTOE3 in the H. caspica assimilating branches was strongly induced by different abiotic stresses, including high salinity, drought, extreme temperature (heat, chilling and freezing) as well as abscisic acid and methyl viologen treatments. Overexpressing HcTOE3 (OE) gene induced transgenic Arabidopsis plant tolerance to freezing stress. Under freezing treatment, the OE lines showed lower content of malondialdehyde (MDA) and electrolyte leakage (EL) and less accumulation of ROS compared with the wild-type (WT). However, the survival rates, antioxidant enzyme activities, and contents of osmotic adjustment substance proline were enhanced in transgenic plants. Additionally, the OE lines increased freezing tolerance by up-regulating the transcription level of C-repeat binding factor (CBF) cold response pathway genes (AtCBF1, AtCBF2, AtCOR15, AtCOR47, AtKIN1 and RD29A) and ABA signal transduction pathway genes (ABI1, ABI2, ABI5 and AtRAB18). Our results suggested that HcTOE3 positively regulated freezing stress and has a great potential as a candidate gene to improve plant freezing tolerance.